The Relationship Of Self Esteem To Resilience In Adolescents In Orphanages - Meli Polaisi; Togi Fitri Afriani Ambarita (Jurnal Ilmu Sosial Mamangan, 2024)
Every individual has the same right to receive proper education as appropriate. However, not all children have a parental figure who can accompany them through life during their physical and mental development. The aim of this research is to determine whether or not there is a relationship between Self Esteem and Resilience in adolescents in orphanages. The research variables discussed in this study include two variables, namely: Independent Variable : Self Esteem Dependent Variable : Resilience The subjects in this research are: Orphanage Teenagers Adolescents with junior high school and high school/vocational school education. The sampling technique used in this research is a non-probability technique , namely proportional sampling with sample data collection based on certain considerations. The results of this research show that the data correlation analysis shows that there is a significant positive relationship between Self Esteem and Resilience in adolescents in orphanages in Medan. The results of correlation testing between Self Esteem and Resilience show a value of r = 760 with p = 0.001 (> 0.05) which means The research hypothesis is accepted, which means, the higher the Self Esteem , the higher the Resilience, and vice versa, the lower the Self Esteem , the lower the Resilience.